'as though nothing were happening—or rather, not happening': Excess and Vacuity in The Little Girls. Issue 1 (May 2021) - Harper, Margaret Mills
Abstract : There's a hole in the middle of Bowen's late novel The Little Girls, literally as well as figuratively: a cavity in the ground dug by three childhood friends for the purpose of burying a secret box. Indeed, the novel is full of holes, from caves and missing treasures to absences, losses, and griefs. At the same time, the book displays a fullness or even extravagant overstuffed quality. Its style, pace, plot, and themes are supersatured, with breathless dialogue, restless activity, and suggestive detail. The Little Girls is very funny even as it never wanders far from catastrophe. The novelistic decision to throw the two modes of comedy and tragedy together is one of the many risks Bowen takes in this novel. She does so as part of a larger meditation on the structures that support art as it frames and thus falsifies, but also acknowledges human lives and history. The Little Girls is about emptiness and loss, but it also suggests that the superfluities and distractions with which people fill their lives have value. This essay pursues several strands of intertextual allusions to find something of what the novel both flamboyantly offers and steadfastly refuses.